2011
DOI: 10.1007/s11051-011-0346-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and hydrothermal deposition of ZnO on silicon: from continuous films to nanocrystals

Abstract: This article presents the study of the electrochemical deposition of zinc oxide from the non-aqueous solution based on dimethyl sulfoxide and zinc chloride into the porous silicon matrix. The features of the deposition process depending on the thickness of the porous silicon layer are presented. It is shown that after deposition process the porous silicon matrix is filled with zinc oxide nanocrystals with a diameter of 10-50 nm. The electrochemically deposited zinc oxide layers on top of porous silicon are sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…Compared to other semiconductor-based gas sensors (SnO 2 , CuO, Cr 2 O 3 , and V 2 O 5 ), PS-based gas sensors operate at comparatively lower temperatures, even at room temperature (RT) [4]. Furthermore, PS manufactured by the semiconducting material is compatible with silicon IC technology that provides the possibility to integrate the PS-based sensing element into any device [4][5][6]. This makes PS a promising gas-sensing material.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to other semiconductor-based gas sensors (SnO 2 , CuO, Cr 2 O 3 , and V 2 O 5 ), PS-based gas sensors operate at comparatively lower temperatures, even at room temperature (RT) [4]. Furthermore, PS manufactured by the semiconducting material is compatible with silicon IC technology that provides the possibility to integrate the PS-based sensing element into any device [4][5][6]. This makes PS a promising gas-sensing material.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide (ZnO) as an instantaneous band gap semiconductor (E g = 3.37 eV) is used in development of gas sensors, optoelectronic devices, photovoltaic devices, and piezoelectrics [5][6][7][8]. Recent observations by Rai et al have shown that the sensing properties of sensors depend on the morphology and surface-to-volume ratio of the sensing materials [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Преимуществом ZnO по сравнению с другими ши-рокозонными полупроводниками (GaN или AlN) яв-ляется возможность получения наноструктур из этого материала различными методами, такими как осажде-ние из газовой фазы, химическое и электрохимическое осаждение, золь-гель и гидротермальный синтез [1,[6][7][8].…”
Section: Introductionunclassified
“…Finally, we used different SiNWs as templates for a deposition of zinc oxide (ZnO) and Ag to fabricate nanocomposites with peculiar optical properties. ZnO in known as a wide-gap semiconductor with outstanding optical properties which can be useful for development of the light emitting diodes [10]. It is very attractive to fabricate effective photoluminescent ZnO/SiNWs nanocomposites as such structures may be integrated with Si wafers.…”
mentioning
confidence: 99%